Evaluating risks and returns of preference shares and the possibilities to introduce an Islamic Proposed formula of preference shares / Zaidun Ahmad - Ahmad, Zaidun (1994)
The shari'ah permits investment of only those shares, bonds and investment certificates which entitled the holder to some of the profits of the company, in proportion to the number of shares held. This position of the shari'ah immediately makes other forms of investment, both short and long term, unlawful because in all cases, income from predetermined return or interest rate are associated in one way or another. As we understand, preference shareholders received a fixed rate of dividends on their holdings which is met before the ordinary share dividends is paid. If the company's profits do not justify paying any dividend, they may also receive nothing. Some companies, however, have preference shares which has the entitlement to a preference dividend carried over until the company is in a position to pay all the arrears. The choice between buying ordinary shares and buying preference shares comes down to the degree of risk which the investors is prepared to bear. The ordinary shares carries a greater risk and, therefore, a greater prospect of high dividends to compensate for the risk. While investment in ordinary shares is perfectly lawful, investment in preference share is not. This is basically due to the similarity between the predetermine dividend rate of return against that of interest payment; both are fixed percentages of the amounts invested.